Epithelial-Mesenchymal Transition in Atopy: A Mini-Review - Anderson, Erik D.; Alishahedani, Mohammadali E.; Myles, Ian A. (Frontiers in Allergy, 2020)
Atopic diseases, particularly atopic dermatitis (AD), asthma, and allergic rhinitis (AR) share a common pathogenesis of inflammation and barrier dysfunction. Epithelial to mesenchymal transition (EMT) is a process where epithelial cells take on a migratory mesenchymal phenotype and is essential for normal tissue repair and signal through multiple inflammatory pathways. However, while links between EMT and both asthma and AR have been demonstrated, as we outline in this minireview, the literature investigating AD and EMT is far less well elucidated. Furthermore, current studies on EMT and atopy are mostly animal models or ex vivo studies on cell cultures or tissue biopsies. The literature covered in this minireview on EMT-related barrier dysfunction as a contributor to AD as well as the related (perhaps resultant) atopic diseases indicates a potential for therapeutic targeting and carry treatment implications for topical steroid use and environmental exposure assessments. Further research, particularly in vivo studies, may greatly advance the field and translate into benefit for patients and families.